Emerging Material Research Trends: Fostering Critical Material Research in Design Students. (May 2022) - Papile, F.; Sossini, L.; Marinelli, A.; Del Curto, B.
Abstract: Sustainable production transition requires new paradigms and strategies, as well as alternative materials. Recently, an increasing number of innovative materials were developed. Such novelties greatly affected the design practice, widening the materic possibilities for designed products. However, traditional material classification does not apply well for these new materials trend. In this paper, the authors cooperated with design students to identify an iterative tracing activity of the new material trends for design, finalised to embed in the same work new tendencies that may rise in future.